Study of Forced Commutation Strategy for Solid State Transfer Switch - 李金元; 赵国亮; 赵波; 张柯; 黄杰 (Kongzhi Yu Xinxi Jishu)
The switch strategy of solid state transfer switch is researched in terms of the mutual effect between solid state transfer switch and power system topology frame respectively. A forced commutation strategy is put forward to 10 kV double-source power system with zigzag grounding transformers. it shortens the switching time of solid-state switch and reduces the switching process on the load.